PENGARUH KUALITAS PRODUK, CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN IPHONE PADA MAHASISWA UNIVERSITAS DIAN NUSWANTORO - Yamisah, Inka Afri; Amalia Nur Chasanah (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Purchasing decisions are consumers' actions in purchasing a product after previously considering and analyzing the information they know about the product based on real experience when seeing it. The purpose of this study is to determine the influence of product quality, brand image and price on iPhone purchasing decisions. The data collection technique in this research was by distributing questionnaires as a sample to a total of 100 respondents. Sampling used a non-probability sampling technique with a purposive sampling method. Based on the results of the t test, the significance level for product quality is 0.000, which is smaller than 0.05. This shows that product quality has a significant influence on purchasing decisions. Brand image has a significance level of 0.00, which is smaller than 0.05, so brand image has a significant influence. Meanwhile, price has a significant level value of 0.000, which is smaller than 0.05, indicating that price has a significant influence on purchasing decisions.